Nonlinear Volterra Integral Equation of the Second Kind and Biorthogonal Systems - M. I. Berenguer; D. Gámez; A. I. Garralda-Guillem; M. C. Serrano Pérez (Abstract and Applied Analysis)
We obtain an approximation of the solution of the nonlinear Volterra integral equation of the second kind, by means of a new method for its numerical resolution. The main tools used to establish it are the properties of a biorthogonal system in a Banach space and the Banach fixed point theorem.